Frontal Fibrosing Alopecia. An Example of Disrupted Aryl Hydrocarbon Receptor-Mediated Immunological Homeostasis in the Skin? - Noakes, Rowland (Clin Cosmet Investig Dermatol, 2020)
Sun protection has been recommended by public health authorities to reduce the risk of keratinocyte and melanocyte tumors, yet some sun exposure is required for vitamin D synthesis. Frontal fibrosing alopecia (FFA) is a cicatricial alopecia that has been reported to have an association with facial photoprotection. The brief review proposes the hypothesis that FFA arises as a result of excessive facial photo-protection with a resultant disturbance in immunological homeostasis mediated via the aryl hydrocarbon receptor-kynurenine pathway axis (AHR/KP) leading to the collapse of immune privilege at the hair bulge.